Ecological Form : System and Aesthetics in the Age of Empire - Steer, Philip; Hensley, Nathan K. (Book collections on Project MUSE., 2019)
"Ecological Form brings together leading voices in nineteenth-century ecocriticism to suture the lingering divide between postcolonial and ecocritical approaches. Together, these essays show how Victorian thinkers used aesthetic form to engage problems of system, interconnection, and dispossession that remain our own. The authors reconsider Victorian literary structures in light of environmental catastrophe; coordinate "natural" questions with sociopolitical ones; and underscore the category of form as a means for generating environmental--and therefore political--knowledge. Moving from the elegy and the industrial novel to the utopian romance, the scientific treatise, and beyond, Ecological Form demonstrates how nineteenth-century thinkers conceptualized the circuits of extraction and violence linking Britain to its global network. Yet the book's most pressing argument is that this past thought can be a resource for reimagining the present."--